Inception meeting for the development of The Gambia Livestock Master Plan by the Ministry of Agriculture - CGIAR Research Program on Livestock (2020)
The Livestock Master Plan inception process for The Gambia was launched in November 2020. ILRI leads the modelling component and sits on the technical committee (see https://www.ilri.org/livestock-master-plans for more information).